Right tree, right place, right time: A visual-functional design approach to select and place trees for optimal shade benefit to commuting pedestrians. (January 2020) - Langenheim, Nano; White, Marcus; Tapper, Nigel; Livesley, Stephen J.; Ramirez-Lovering, Diego
Highlights: A performance-based design approach to enable visual-functional decisions on urban treescapes. Simulated tree shade benefits of streetscape design scenarios. Spatially explicit modelling and visualisation of treescape design and ecosystem service. Optimised tree shade benefit to encourage active school journeys by school children. Abstract: Australia tops the world's charts in occurrence of skin cancer and intensity of heat waves, while concurrently achieving high childhood obesity levels, due in part to low rates of physical activity. These issues converge in the challenge of protecting school children from heat and ultra-violet light exposure whilst simultaneously encouraging them to select active modes of transport for school journeys. This paper describes a new performance-based tree-scape design approach for quantifying shaded walking routes using the pedestrian accessibility modelling tool "PedestrianCatch", combined with visual-functional tree-scape modelling for both solar impact analysis and qualitative aesthetic outcomes of different street tree-scape designs. We test this design approach on a precinct surrounding a school as a case study. The study results demonstrate the potential for targeted strategic street tree selection and planting in proximity to schools, providing the co-benefits of improved thermal comfort and reduced solar and ultra-violet exposure of children walking home from school. This performance-based design approach offers local government, public health and education departments with a way to mediate multiple and divergent concerns for climate amelioration, transport choices and population health by planting the right tree, positioned to provide shade in the right place at the right time .